A study of optimum currency area in East Asia: a cluster analysis - Ibrahim, Saifuzzaman (Center for Economic Integration, Sejong Institution, Sejong University, 2008)
This paper studies the feasibility of ASEAN+3 Monetary Union by investigating the homogeneities of the countries. Utilizing techniques of cluster analysis on two sets of criteria, the Optimum Currency Area (OCA) and the adjusted Maastricht Treaty (MTC), reveals that homogeneities of ASEAN+3 are low and the immediate formation of a monetary union would entail serious potential costs. Furthermore, our findings suggest that grouping differ between pre-crisis and post-crisis periods which could be due to the different impact of the crisis on the economic structure of these countries.